2020
DOI: 10.1007/s00403-020-02053-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pediatric hidradenitis suppurativa: a cross-sectional multicenter study of 140 patients

Abstract: Hidradenitis suppurativa (HS) rarely affects pediatric patients. The literature on pediatric HS patients is scarce. This is a cross-sectional study based on case note review or interviews and clinical examination of 140 pediatric patients undergoing secondary or tertiary level care. Patients were predominantly female (75.5%, n = 105) with a median age of 16. 39% reported 1st-degree relative with HS. Median BMI percentile was 88, and 11% were smokers (n = 15). Median modified Sartorius score was 8.5. Notable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 58 publications
11
33
1
Order By: Relevance
“…14 Other studies on pediatric HS reported sex, family history, and "early" or prepubertal-onset disease as relevant factors impacting on disease severity, extent of involvement, and clinical distribution of lesions. 15,16 We report a large pediatric cohort of HS patients, describing clinical characteristics, comorbidities and treatment patterns, further confirming a disease continuum with the adult patient group. Female preponderance (female:male ratio 3.6-4 to 1) is remarkably higher in pediatric than in adultonset HS and has been reported in both international and national observational studies.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…14 Other studies on pediatric HS reported sex, family history, and "early" or prepubertal-onset disease as relevant factors impacting on disease severity, extent of involvement, and clinical distribution of lesions. 15,16 We report a large pediatric cohort of HS patients, describing clinical characteristics, comorbidities and treatment patterns, further confirming a disease continuum with the adult patient group. Female preponderance (female:male ratio 3.6-4 to 1) is remarkably higher in pediatric than in adultonset HS and has been reported in both international and national observational studies.…”
Section: Discussionsupporting
confidence: 56%
“…14 Other studies on pediatric HS reported sex, family history, and “early” or prepubertal-onset disease as relevant factors impacting on disease severity, extent of involvement, and clinical distribution of lesions. 15,16…”
Section: Discussionmentioning
confidence: 99%
“…highlight that although only one out of five paediatric patients smoked actively, a passive tobacco exposure was documented by the rest of the patients. A current retrospective analysis from Riis et al 24 . showed that almost 50% of the paediatric patients were passive smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, obesity was prominent in pediatric patients and was related to parent BMI, indicating that there may be benefit in implementing preventative measures in the whole family 18 . Lastly, the way in which disease was managed in pediatric patients was similar to that in adult patients, but younger patients more commonly exhibited milder disease 19 .…”
Section: Epidemiologymentioning
confidence: 97%